OCT-angiography detects longitudinal microvascular changes in glaucoma: a systematic review. Issue 5 (15th January 2021) - Miguel, Ana; Silva, André; Barbosa-Breda, Joao; Azevedo, Luis; Abdulrahman, Abdulkarim; Hereth, Esther; Abegão Pinto, Luis; Lachkar, Yves; Stalmans, Ingeborg
Abstract : Background/aims: Optical coherence tomography angiography (OCTA) allows the study of vessel density (VD). We intended to perform a systematic review of studies focusing on longitudinal changes in peripapillary and macular VD measurements in glaucoma. Methods: A search was performed across MEDLINE, Scopus, ISI Web of Science and Google Scholar, using the following query from inception until 20 September 2019: (("optical coherence tomography angiography"[tiab]) OR (optical coherence tomography angiography[MeSH]) OR ("OCTA"[tiab]) OR ("OCT-A"[tiab]) OR ("angio-OCT"[tiab]) OR ("OCT- angiography"[tiab]) OR ("OCT-angio"[tiab]) OR ("OCT-angiographie"[tiab])) AND (glaucom*[tiab] OR glaucoma[MeSH]). Prospective studies that quantitatively assessed the longitudinal changes in VD in glaucoma with at least 3 months of follow-up were included. Results: Ten out of 4516 studies were included. The rate of VD change in glaucoma varied from 0.036/year to 1.08/year and 1.3% to 3.2% per year, with significantly different rates between glaucoma and healthy controls. Five studies assessed VD change after glaucoma surgery, obtaining variable results, ranging from a temporary VD decrease to increase after 3 months. Meta-analysis was not possible due to a wide variation in methods, measurements and region of VD. Conclusion: OCTA is a non-invasive technology, which shows promise in glaucoma. Measures should be taken to increase the quality and standardise the methodology of VD measures in OCTA longitudinal studies, for future meta-analyses.